MEMBACA NILAI KEMANUSIAAN DALAM NOVEL AUTOBIOGRAFI - Sayuti, Suminto A.; Wiyatmi, Wiyatmi; Budiyanto, Dwi (Diksi, 2019)
(Title: Reading the Value of Humanity in Novel Autobiography). This article aims at revealing and elaborating the values of humanity embedded in the authobiography novels by Indonesian writers. The study is rooted in the fact that authobigraphy novels are currently burgeoning in Indonesia. Four novels selected for this study are Kenang- kenangan Hidup (Hamka), Habibie-Ainun (B.J. Habibie), Kehilangan Mestika (Hamidah), and Manusia Bebas (Soewarsih Djojopuspito). From the authobiography novels, readers, young generation in particular, can learn the values of life that the authors make as their vision to live life and its creativity processes, which cannot be separated from historical, social and political contexts. Through their authobiography novels, the authors express not only their conscience, emotion, and ideas, but also the ideology that they hold to live life and to realize their vision in the future.Key word: authobiography, humanity, creativity processes